South–South Cooperation and Neoliberal Hegemony in a Post‐aid World. Issue 3 (24th March 2018) - Morvaridi, Behrooz; Hughes, Caroline
ABSTRACT: The current iteration of South–South Cooperation (SSC) differs fundamentally from the first manifestation in the early 1970s, largely because of differences in assumptions about who is cooperating with whom and to what end, in the context of SSC. These differences are significant for the material practice of SSC and the ideological function of SSC rhetoric. In this article, the authors argue that contemporary ideas about SSC do not retrieve the radical potential of the original formulation, but rather expand the hegemonic neoliberal world order into a new phase through a reframed idea of the relationships between North and South and between states and markets. This promotes a new common‐sense understanding of the contemporary international political economy while further depoliticizing the idea of development. It hijacks the critical force of dependency theory, harnessing the terminology of the 1970s and a nostalgia for state‐led development to an ideological fix that in fact shores up the neoliberal world order in the context of a potentially destabilizing shift in the functioning of global capital.